THE MAJOR FACTORS WHICH CONTRIBUTED TO THE TRANSFORMATION OF TAIAN FROM A PRIMITIVE AGRICULTURAL SOCIETY TO ONE OF THE NWLY INDUSTRIALIZING COUNTRIES(NICS) IN ASIA - Jangkung Handoyo Mulyo (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2000)
The major factors which contributed to the transformation of Taiwan from a primitive agricultural society to one od the newly industrializing countries (NICS) in Asia.